Digitalisasi Pengelolaan Biaya Produksi Menggunakan Metode Harga Pokok Pesanan Pada Industri Manufaktur - Andi Riyanto; Galuh Intan Rakasiwi; Eva Marsusanti (Artikel Ilmiah Sistem Informasi Akuntansi, 2022)
This research was conducted at PT. Sarandi Karya Nugraha which is a medium-scale manufacturing industry that produces medical devices. This manufacturing industry carries out its production activities based on orders. The purpose of this research is to analyze the process of determining production costs based on orders and to design an information system application as a solution to overcome the problems that exist in the company. The problems in this study are the inaccuracy of calculations and ineffectiveness in determining production costs by using the cost-of-order method in accordance with generally accepted accounting standards. Methods of collecting data are direct interviews with company owners and observations to determine the required system design as well as through literature study. The system development method uses the waterfall model. The results of this study are in the form of a computerized information system to facilitate stakeholders in determining production costs based on orders and facilitate the manufacture of reports that are useful for decision makers so that it is hoped that this system can be more effective and efficient in assisting company operations compared to the manual system applied in the current company.